Influence of Preheating Procedure and Polymerization Modes on Degree of Conversion of Contemporary Resin Composites - Mutlu Özcan; Başak Yazkan; Nilgün Akgül; Ahmet Erdem; Özge Gizem Yenidünya (Current Research in Dental Sciences)
Objective: To evaluate the effects of preheating procedure and polymerization modes on degree of conversion (DC) of resin composites.Methods: Three different types of composites - a conventional (GrandioSO - [GSO]), a bulkfill (GrandioSO x-tra - [GSX]), and a thermoviscous bulkfill (VisCalor bulk - [VCB]) - were investigated. Three specimens were prepared for each combination of the variables (composite type*preheating procedure*polymerization mode). Photo-polymerization was performed using an LED operated in standard (SM), high power plus (HM), and x-tra power (XM) modes. DC was measured with Fourier Transform Infrared Spectroscopy after 5 min and 24 h post-irradiation. Furthermore, three-way analysis of variance followed by a Tukey test at a significance level of P <.05 were performed to compare the DC values.Results: Considering the DC values at two post-irradiation time, preheated VCB group polymerized with HM gave the highest DC value, while GSX cured with XM, regardless of the preheating exhibited the lowest one. Preheating application caused a statistically significant increase in the DC values of the VCB*SM, VCB*HM, and GSO*HM groups at both evaluation periods, and the GSX*SM group at 24h post-irradiation. Regarding the polymerization mode, the ranking depending on the significant differences among all preheated composites tested at both time intervals was HM > SM > XM.Conclusion: Preheating generally exhibited favorable effects on the DC of all tested composites, with the most significant impact observed in VCB. Additionally, polymerization with x-tra power mode is not recommended to achieve a sufficient DC required for clinically acceptable restorations.Keywords: bulk fill composite; degree of conversion; FTIR; polymerization mode; preheating; thermoviscousity